Comorbid Neurodegeneration in Primary Progressive Aphasia: Clinicopathological Correlations in a Single-Center Study. (8th September 2022) - Rusina, Robert; Bajtosova, Radoslava; Cséfalvay, Zsolt; Keller, Jiri; Kavkova, Anna; Kukal, Jaromír; Matej, Radoslav
Abstract : Introduction . Primary progressive aphasia (PPA) is a clinically variable syndrome manifesting as slow progressive loss of speech and language with multiple underlying neurodegenerative pathologies. Materials and Methods . We included data from nine PPA patients with available autopsies. We then retrospectively reviewed all available medical records, neuropsychology, and MRI results to confirm the corresponding subtypes of PPA and compared them with postmortem neuropathological results. Results . Clinical presentations corresponded to the nonfluent/agrammatic variant in six cases, the semantic variant in one case, the logopenic variant in one case, and the mixed variant (concomitant nonfluent/agrammatic plus semantic variant) in one case. Patients with a broader clinical presentation, i.e., combining manifestations of one PPA subtype and symptoms of another PPA variant, had autopsy comorbidities showing multiple neurodegenerative disorders. Of the nine subjects enrolled in the study, Alzheimer's disease (AD) was found in eight cases; however, in only one case, AD was detected as an isolated neuropathological substrate of PPA. In eight brain samples, different comorbid neuropathologies were detected: three cases with comorbid AD and dementia with Lewy bodies, two cases with comorbid AD and TDP-43 pathology, one case with comorbid AD and complex tauopathies, and one case with comorbid AD with both tau and TDP-43 deposits. Finally, one case had comorbid tau and TDP-43 pathology but without comorbid AD pathology. Conclusions . Our observation suggests that PPA cases could be more heterogeneous in their etiology than previously thought and underlying neurodegenerative comorbidities should be considered in routine practice, especially if the clinical presentation of PPA is atypical.